(3GdTaGA aj GdefWbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3Ydi bdi Hf MSjf bdi s)
(3ChdgG (B:s
(3GdfbWI eG dG hGdNW HdG YQV hWQaGg fbWJGf hGdNW GdeSJbje Ydi ESJbHGd cd fbWI jYQV ajg dfbWJi WQajI s
(3BNQgG (B:s
(3hef ELJeYJ dg eYgG GdMceI GdfXQjI abO SYO hCef aGR eY Pdc HGdNhGU GdfHhjI cGO jUjQ HEfSGfjkG acGO Cf jMd YHGOJg HYO Gddg JYGdi hgh SdWGf GdYGde GdCQV hNdjaI Gddg ajgG hGdMeO ddg QH GdYGdejf s
(3GdQjGVjGJ hGdEdgjGJs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs